2010
DOI: 10.2341/10-012-l
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Conversion of Luting Resins Around Ceramic Inlays in Natural Deep Cavities: A Micro-Raman Spectroscopy Analysis

Abstract: Clinical RelevanceContrary to previous evidence, the degrees of conversion of resin luting materials have been shown to reach statistically similar values in three different depths around ceramic inlays luted to natural cavities. Both dual-cure and light-cure materials have presented conversion homogeneity, although they have been shown to be material-dependent. SUMMARYThis study evaluated the degree of conversion (%DC) of luting agents around ceramic inlays placed in deep natural cavities. Thirty-six cylindri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
(52 reference statements)
1
15
0
4
Order By: Relevance
“…The properties of lightcured cements are influenced by the thickness and composition of the ceramic used. This thickness affects the transmission of light [3] and its quality reaching the underlying cement layer [28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…The properties of lightcured cements are influenced by the thickness and composition of the ceramic used. This thickness affects the transmission of light [3] and its quality reaching the underlying cement layer [28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The extent of the monomer-to-polymer conversion during the polymerisation process is expressed as the degree of conversion (DC) and can be studied by Raman spectroscopy, which measures the C=C double bond's stretching vibrations on the compo-site surface. 5,6 Consequently, the DC is directly related to the mechanical properties of the composites and their clinical performance. 7,8 Free radicals are reactive chemical species with an unpaired electron.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the use of these light-activated cements should be limited to some clinical situations such as inlays, veneers and onlays, in which the thickness and shade of restoration do not affect the ability of light to reach and activate the cement 15 . Considering the light-activated resin cements for veneers and onlays cementation, the polymerization quality is related to several factors such as photo-activation light source, irradiance, irradiation time, material composition and light attenuation caused by ceramic 11,[13][14][16][17][18] . It was observed that the transmittance of light through ceramic decreases as function of the material interposed between the light source and the resin cement 19 .…”
Section: Introductionmentioning
confidence: 99%